Panoramic view of the occurrence of Yersinia species other than Y. pestis in Brazil - Falcão, Juliana Pfrimer; Corrêa, E. F. [UNESP]; Martins, C. H G; Falcão, D. P. [UNESP] (My University, 2008)
Data on the occurrence of Yersinia species, other than Y. pestis in Brazil are presented. Over the past 40 years, 767 Yersinia strains have been identified and typed by the National Reference Center on Yersinia spp. other than Y. pestis, using the classical biochemical tests for species characterization. The strains were further classified into biotypes, serotypes and phagetypes when pertinent. These tests led to the identification of Yersinia cultures belonging to the species Y. enterocolitica, Y. pseudotuberculosis, Y. intermedia, Y. frederiksenii and Y. kristensenii. Six isolates could not be classified in any of the known Yersinia species and for this reason were defined as Non-typable (NT). The bio-sero-phagetypes of these strains were diverse. The following species of Yersinia were not identified among the Brazilian strains by the classical phenotypic or biochemical tests: Y. aldovae, Y. rhodei, Y. mollaretti, Y. bercovieri and Y. ruckeri. The Yersinia strains were isolated from clinical material taken from sick and/or healthy humans and animals, from various types of food and from the environment, by investigators of various Institutions localized in different cities and regions of Brazil.
Keywords: Brazil; Occurrence; Yersinia spp.; water; bacterial virulence; bacterium culture; bacterium identification; bacterium isolation; biotype; food analysis; food contamination; human; nonhuman; phenotype; review; serotype; water analysis; Yersinia; Yersinia aldovae; Yersinia bercovieri; Yersinia enterocolitica; yersinia frederiksenii; yersinia intermedia; yersinia kristensenii; Yersinia mollaretti; Yersinia pestis; Yersinia pseudotuberculosis; Yersinia rhodei; Yersinia ruckeri; yersiniosis